Efficient energy transfer from zinc oxide nanocrystals to europium (3+) and terbium (3+) ions embedded in an oxide matrix - Mangalam, Vivek (2019)
This thesis presents the study of energy transfer from Zinc Oxide Nanocrystals (ZnO-nc) to two different types of rare-earth (RE) ions, namely Europium (III) (Eu3+) and Terbium (III) (Tb3+) ions. RE ions, such as Eu3+ and Tb3+, are important materials which have been extensively studied for their applications in lighting and display technologies. Eu3+ and Tb3+ ions have been used for red and green light emitting devices due to sharp red emission at 614 nm and sharp green emission at 545 nm, respectively. However, the RE ions have their limitations. For instance, a specific excitation wavelength is required to excite a specific type of RE ion (e.g. 392 nm excitation wavelength is preferred to excite the Eu3+ ions while 348 nm is preferred to excite the Tb3+ ions). This makes excitation difficult in samples with more than one type of RE ions (e.g. to produce white light emitting sample with Eu3+ and Tb3+ ions) as different wavelengths are required to excite different types of RE ions. Furthermore, the RE ions have low absorption cross-section. These difficulties can be overcome by using ZnO-nc nanocrystals as sensitizers to excite the RE ions. ZnO is a wide band gap semiconductor which emits light in blue and ultraviolet (UV) region of the electromagnetic spectrum. ZnO-nc have two main advantages, i) they have much higher absorption cross-section compared to the RE ions and ii) they can be excited using any wavelength above the optical band gap of ZnO-nc, hence specific excitation wavelength is not required. Thus, the ZnO-nc can be easily excited compared to the RE ions, which can then efficiently transfer the energy to RE ions, which in turn emit light through radiative de-excitation. ZnO-nc is also an attractive sensitizer as can excite a wide variety of RE ions like Eu3+, Tb3+, Ce3+, Er3+, Yb3+, Ho3+ and Dy3+. Although, various studies show energy transfer from ZnO-nc to Eu3+ ions and ZnO-nc to Tb3+ ions, a complete understanding of the energy transfer mechanism is still lacking to further develop energy efficient light emitting devices using these materials. For instance, studies on energy transfer contribution from ZnO-nc to RE ions, energy transfer efficiency from ZnO-nc to RE ions and effect of interaction distance between ZnO-nc and RE ions on energy transfer needs to be investigated. Furthermore, a white light emitting device using emission from ZnO-nc together with Eu3+ ions and Tb3+ ions has also not been reported. In this work, the low cost sol-gel technique was used to develop thin film samples of ZnO-nc embedded in SiO2 matrix co-doped with RE ions like Eu3+ and Tb3+ to address and study the above mentioned points which are currently lacking. The material characterisation was done by studying the photoluminescence (PL) emission, photoluminescence excitation (PLE) and time-resolved photoluminescence (TRPL) emission from the thin film samples. In this work, the author clearly shows energy transfer from ZnO-nc to Eu3+ ions and Tb3+ ions. The excitation of Eu3+ ions through energy transfer from ZnO-nc is shown to be almost 7 times higher than the direct excitation of Eu3+ ions. The author also identified that the excitonic emission of ZnO-nc at 378 nm and Zn defect emission at 396 nm have the highest energy transfers contribution in exciting the Eu3+ ions and that the energy transfer efficiency of these emission centers were calculated to be more than 60%. Similarly, the band edge emission from ZnO-nc at 360 nm and excitonic emission at 378 nm have the highest energy transfer contribution to Tb3+ ions with transfer efficiency of 35% for both the emission centers. In another study on the effect of interaction distance on the energy transfer process, it was shown that the distance of 5.11 nm between ZnO-nc and Eu3+ ions is the optimum distance for energy transfer. Finally, the author also fabricated a white light emitting sample in this work by combining the emission of Eu3+, Tb3+ and ZnO-nc emissions. The concentration of Eu3+ and Tb3+ ions for the white light emitting sample was found to be 1.2 mol% and 2.4 mol%, respectively, though simulation which was confirmed by fabricating the sample. The results from these works are important and can help in the development of future proficient red, green and white luminescent solid state devices based on a low-cost sol-gel technique. Extending these key analyses to systems with other rare earth elements will also help in making efficient light sources for wide ranging photonics applications like lasers, optical amplifiers, lighting and display technologies.